Variation of mitochondrial size during the cell cycle: A multiparameter flow cytometric and microscopic study - Kennady, P. Kavin; Ormerod, M. G.; Singh, Shashi; Pande, Gopal (Cytometry. Part A, 2004)
Background Changes in mitochondrial structure and size are observed in response to alterations in cell physiology. Flow cytometry provides a useful tool to study these changes in intact cells. We have used flow cytometry and digital fluorescence microscopy to analyze the variations in mitochondrial size in relation to specific phases of the cell cycle. Methods Supravital staining of rat fibroblasts was done with Hoechst 33342 and rhodamine 123, and cells were analyzed in a dual‐laser flow cytometer. Synchronized cells at various stages of the cell cycle were analyzed for changes in mitochondrial size. These cells were also examined by electron microscopy, digital fluorescence microscopy and computerized image analysis to compare the lengths of the mitochondria. Results By using fluorescence pulse width analysis, we observed two populations of mitochondria in intact cells. The percentage of cells with small and large mitochondria at specific stages of the cell cycle indicated that mitochondrial size increases during the cell cycle; early G1 phase cells had the smallest mitochondria and the mitotic phase cells had the largest mitochondria. These results were confirmed by microscopic analysis of cells. Conclusions Flow cytometry can distinguish the relative mitochondrial size in intact cells, and in combination with digital microscopy it can be used to study mitochondrial variation during the cell cycle. © 2004 Wiley‐Liss, Inc.